Konsep Pendidikan Karakter dalam Perspektif Al-Qur'an: Analisis Tematik Surat Luqman Ayat 12-19 - Za’far Siddik, Rasyid; Fuad Ruhiyat, Ahmad; Athoillah Yusuf, Ibnu; Sulaeman, Rudi; Sofian (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Singaperbangsa Karawang, 2025)
Moral crisis and character degradation among the younger generation in the digital era pose a serious challenge to the education world, which has predominantly focused on cognitive aspects. This research aims to explore the ideal concept of character education through a thematic analysis of Surah Luqman verses 12-19. Employing a qualitative research method with a library research approach and the